The Effects of Rice Husk Ash and Dolomite on Soybean Yield at Latosol Soil - Aditya Perdanatika; Suntoro Suntoro; Pardjanto Pardjanto (Universitas Sebelas Maret, 2018)
The aim of this research is to evaluate the effects ofrice husk ash and dolomite application on soybean yield at latosol soil. This research was conducted at a plastic house from September to December 2016. This research employed Factorial Randomized Complete Design with two factors and three replications. The first factor is the dosage of rice husk ash, consisted of four levels (0 (control), 3.75 ton ha-1, 7.5 ton ha-1 and 15 ton ha-1), and the second factor is the dosage of dolomite consisted of three levels (0 (control), 250 and 500 kg ha-1, respectively). The results found that the application of 15 tons ha-1 rice husk significantly affected the number of full pods and total pods, but did not affect the number of the empty pods. The application of 3.75 tons ha-1 husk ash increased the seed weight and weight of 20 dry seeds. It was also found that the higher the rice husk ash dose applied, the more root nodules produced.